The Federal Reserve's market functioning purchases - Michael J. Fleming; Haoyang Liu; Rich Podjasek; Jake Schurmeier (Federal Reserve Bank of New York, 2021)
In March 2020, massive customer selling of U.S. Treasury securities and agency mortgage-backed securities (MBS) triggered by the COVID-19 pandemic overwhelmed dealers' capacity to intermediate trades, contributing to a marked deterioration of market functioning. The Federal Reserve promptly took numerous steps to address the market disruptions, including the initiation of market functioning purchases of Treasury securities and agency MBS. Purchases quickly expanded to over 100 billion per day as the Fed announced plans to buy securities "in the amounts needed" to support market functioning and the effective transmission of monetary policy. Market liquidity improved steadily after mid-March, suggesting that the Fed's efforts were effective, and the security purchases were scaled back accordingly.
Keywords: E53; E44; G12; G01; 330; Federal Reserve; asset purchases; Treasury securities; agency mortgage-backed securities; COVID-19